Extracranial neurogenic tumors of the head and neck, - Curioni,Otávio Alberto (2015)
ABSTRACT INTRODUCTION: Peripheric nerve tumors typically derive from Schwann cells of the peripheral nerve sheet. Since these tumors are uncommon, they should be considered in preoperative differential diagnosis. OBJECTIVE: To report the experience of a tertiary care department. METHODS: Forty-two patients with head and neck peripheral neurogenic tumors were retrospectively analyzed and evaluated from 1977 to 2013. The preoperative diagnosis was confirmed by biopsy or imaging study. RESULTS: The mean age was 41.7 and 15 patients (36%) were male. The mean size was 5.5 cm and 26 (61%) were located laterally in the neck. Most tumors (39.9%) presented as an asymptomatic neck mass. Most (39.9%) were resected through a neck approach. Cranial nerves were the commonest site of origin. CONCLUSIONS: Extracranial neurogenic tumors presented with a mean size of 5.5 cm, were located laterally in the neck, normally had their origin from cranial nerves, and their resection approach is cervical.